Blood Proteins Strongly Reduce the Mobility of Artificial Self‐Propelled Micromotors. Issue 49 (25th October 2013) - Wang, Hong; Zhao, Guanjia; Pumera, Martin
Abstract Autonomous self‐propelled catalytic microjets are envisaged as an important technology in biomedical applications, including drug delivery, micro/nanosurgery, and active dynamic bioassays. The direct in vivo application of these microjets, specifically in blood, is however impeded by insufficient knowledge on the in vivo viability of the technique. This study highlights the effect of blood proteins on the viability of the microjets. The presence of blood proteins, including serum albumin and γ‐globulins at physiological concentrations, has been found to dramatically reduce the viability of the microjets. The reduction of viability has been measured in terms of a lower number of active microjets and a decrease in the velocity of propulsion. It is clear from this study that in order for microjets to function in biomedical applications, different modes of propulsion besides platinum‐catalyzed oxygen bubble ejection must be employed. These findings have serious implications for the biomedical applications of catalytic microjets.